EFFECTIVENESS OF PROBIOTICS SUPPLEMENTED LINSEED MEAL BASED DIETS ON OVERALL PERFORMANCE OF LABEO ROHITA - M. M. Shahzad; K. Akhter; S. M. Hussain; Z. Hussain; M. Y. Zahoor; N. Ahmad; F. Khalid; M. T. Rafique (Journal of Animal and Plant Sciences, 2022)
Probiotics have positive effects on the host by inhibiting pathogenic microorganisms, improving feed intake, contributing enzymatically to digestion, secreting growth-promoting factors and improving the quality of pond water. Seventy days research trial was performed to check the efficacy of prob-added linseed meal based (LMB) diet on overall performance including growth, mineral absorption and digestibility of nutrients in Labeo rohita fingerlings. By using various concentrations of probiotics (0, 1, 2, 3, 4, 5 g/kg) six test diets were prepared. All six groups were fed twice a day, their faeces samples were collected on daily basis and stored for chemical analysis. Results of current research revealed that probiotics addition showed significant improvement in fish. Highest weight gain (20g), weight gain% (279%), SGR (1.48) and best FCR (1.21) was found in fish fed 2 g/kg level of prob-added LMB diet. Similarly, highest nutrient digestibility (CP; 71% and Fat; 75%) and mineral absorption (P; 72%, K; 75% and Na; 76) were also analyzed in the juveniles that fed with the above said test diet. Whereas maximum digestibility of GE (74%) and minerals absorption (Ca; 73%, Al; 69%) was observed maximum at test diet IV that was supplemented with 3 g/kg LMB diet. On the basis of these results, it was concluded that 2g/kg level of probiotics inclusion was optimum for the formulation of ecofriendly and economically affordable fish diet by using LMB diet.
Keywords: Probiotics; Growth performance; Digestive enzymes; Nutrient digestibility; Minerals